Anticancer Properties of Lycopene - Şahin, Kazım; Orhan, Cemal; Şahin, Nurhan; Küçük, Ömer (Springer Science and Business Media B.V., 2019)
Lycopene is an acyclic isomer of beta-carotene, found in red-colored fruits and vegetables, including tomatoes, and their processed products, watermelon, papaya, guava, carrots, red grapefruit, and sweet potatoes. It is synthesized by plants or autotrophic bacteria but not by animals. This work provides an up-to-date overview of mechanisms linking lycopene in the human diet and cancer, considering epidemiological, clinical studies, and experimental data. Dietary lycopene supplementation may reduce the risk of cancers of many organs such as prostate and at the same time retard the growth of tumors. The main protection properties of lycopene against cancer include antioxidant, anti-inflammatory, anti-inhibitory of cancer cell proliferation, anti-apoptotic, increased gap-junctional communication, interferences in insulin-like growth factor 1 receptor signaling pathways, and cell cycle progression and, the ability to improve the metabolic profile. In this context, lycopene has been shown to exert a protective effect in humans or animals with cancers including prostate, breast, gastric, colon, pancreatic, renal, and several other cancers in many studies, although the obtained results are sometimes inconsistent, which warrants further studies focusing on its bioactivity. In this chapter, lycopene supplementation in cancer prevention is reviewed and possible mechanisms of action are discussed in detail. © 2019, Crown.
Keywords: Cancer; Lycopene; Molecular mechanism; Nutrition; Prevention